In vitro copper-chelating properties of flavonoids - Ríha, Michal; Karlícková, Jana; Filipský, Tomáš; Jahodár, Ludek; Hrdina, Radomír; Mladenka, Premysl (Free radical biology & medicine, 2014)
Copper is an indispensable trace element for human body and the association between a disruption of copper homeostasis and a series of pathological states has been well documented. Flavonoids influence the human health in a complex way and the chelation of transient metal ions indisputably contributes to their mechanism of the action, however, the information about their copper-chelating properties have been sparse. This in vitro study was thus aimed at the detailed examination of flavonoids-copper interactions by two spectrophotometric assays at four (patho)physiologically relevant pH conditions (4.5-7.5), with the emphasis on the structure-activity relationship. The tested flavonoids were compared with the clinically used copper chelator, trientine. Most of the 26 flavonoids chelated copper ions, however, in a variable extent. Only flavones and flavonols were able to form stable complexes with both cupric and cuprous ions. The 3-hydroxy-4-keto group and 5,6,7-trihydroxyl group represented the most efficient chelation sites in flavonols and flavones, respectively, and the 2,3-double bond was essential for the stable copper chelation. Interestingly, the 3´,4´-dihydroxyl (catechol) group was associated only with a weak activity. Although none of the tested flavonoids were more potent than trientine at physiological or slightly acidic conditions, 3-hydroxyflavone, kaempferol and partly baicalein surpassed trientine at acidic conditions. Conclusively, flavonoids containing appropriate structural features were efficient copper chelators and some of them were even more potent than trientine under acidic conditions.